Medical decision-making on behalf of a patient who lacks capacity when treatment is deemed to be "futile": who ought to determine that a treatment is futile, and how ought this decision to be made? (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Recent case-law in England has considered the statutory guidelines in regards medical decision-making for patients who lack the capacity to make their own treatment decisions, and has tackled the further difficulty that arises when these interventions are described as being ‘futile’. The absence of absolute definitions of such concepts allows for disparate legal and moral interpretation, and it is understandable that the difficulty in reaching consensus on such theoretical issues has spilled over into everyday clinical practice. Who ought to decide that a treatment is futile? Is the ‘best interests’ standard appropriate for such end-of-life decision-making? As an objective professional, is the doctor not best positioned to decide what constitutes futile treatment? Respect for a patient’s autonomy suggests that the patient should make this decision. Other moral imperatives must be considered too: for example, when the harms of medical treatment outweigh its benefits, how should the doctor act in order to ‘do no harm’? Whatever solutions are proposed, unilateral decision-making of any kind (even with the best intentions) arguably cannot provide a sufficiently balanced assessment of such predicaments. When a patient is unable to decide for herself†, it seems appropriate to ask someone removed from the doctor-patient partnership to assist with decision-making. Are persons closest to the patient suitable for this role, or should we rely on a reasonable person in society, or perhaps even a specialist from any religious or secular, medico-legal or bioethical field? But value judgements pervade medical decision-making, and even the diligent application of legal and moral principles cannot guarantee impartial outcomes. All things considered then, the overall benefit to the patient may be achieved when experts in ‘the patient’, medicine, bioethics and law seek consensus on what constitutes the best interests of that particular patient at that particular time.
Keywords: futility; futility; capacity; capacity; autonomy; autonomy; paternalism; paternalism; multidisciplinary team; multidisciplinary team